2013
DOI: 10.1158/2159-8290.cd-13-0076
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Primary Melanoma of the CNS Implicates NRAS

Abstract: Summary :In this issue of Cancer Discovery , Pedersen and colleagues present the fi rst mouse model of primary CNS melanoma, which arises when oncogenic NRAS is expressed from the endogenous Nras promoter in melanocytes during embryogenesis. In support of this model, two pediatric cases of NRAS -mutant primary melanoma of the CNS are identifi ed. Cancer Discov; 3(4); 382-3. ©2013 AACR.See related article by Pedersen et al., p. 458 (6).Melanoma can be subdivided into categories based on body location, and some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2016
2016

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
0
2
0
1
Order By: Relevance
“…Although NRAS is rarely involved in primary melanoma of CNS, it is suggested that this model could represent some of the rare cases. 101 …”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although NRAS is rarely involved in primary melanoma of CNS, it is suggested that this model could represent some of the rare cases. 101 …”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…Although NRAS is rarely involved in primary melanoma of CNS, it is suggested that this model could represent some of the rare cases. 101 PTEN/BRAF models. Identification of the PTEN deletion and BRAF mutations were two of the greatest discoveries in melanoma field.…”
Section: Genetically Engineered Mouse Modelsmentioning
confidence: 99%
“…3) Teoría neurogénica: las células pigmentadas se derivan de la cresta neural y pueden originar tumores 3 . También se han reportado anormalidades cromosómicas, como la deleción o rotura en el brazo largo y corto del cromosoma 6, con una posible pérdida en la función de genes supresores tumorales en el melanoma maligno primario del sistema nervioso central 15 , y se han diseñado modelos experimentales en ratones que demuestran la función de oncogenes 16,17 y la aparición de melanoma maligno primario del sistema nervioso central en ratones cuando el oncogén NRAS es expresado en melanocitos durante la embriogénesis por medio de un promotor NRAS endógeno 18 . Se sabe que este oncogén induce proliferación de melanocitos y lesiones melanocíticas congénitas en humanos.…”
Section: Figuraunclassified